implications of adding chitosan and glycerol to edible film from sweet potato starch on tensile strength - Wijaya, Kevin; Tantra Diwa Larasati (Prodi Kimia, 2025)
The use of inappropriate plastic in food packaging can pose risks to human health, including the potential for cancer, because the plastic raw materials come from natural gas and petroleum. Even though it is still used, the use of this material is starting to be reduced because its impact is not environmentally friendly and has the potential to be detrimental to health. One innovation that can be implemented is the use of edible organic plastic, such as edible film. The development of edible film materials involves polymer compounds from plants, such as starch. This research aims to find the best formulation for making edible film using various variations of chitosan addition. Edible film is made from sweet potato starch with the addition of 3% variable composition chitosan; 4%; 5% (w/v) and glycerol (3%). Tests show that the higher the chitosan content in starch, the Tensile Strength (TS) of edible film will increase. Findings from the research show that the best edible film is produced from sweet potato starch with a chitosan variation of 5% (w/v).